PENDAMPINGAN PENINGKATAN KEMAMPUAN LITERASI DAN NUMERASI PADA SISWA SDN 1 MANGIR KECAMATAN ROGOJAMPI KABUPATEN BANYUWANGI - Trio Ageng Prayitno; Nuril Hidayati; Yuskil Mushofi; Kistantia Elok Mumpuni (JPM PAMBUDI, 2022)
Based on a joint agreement between the community service team and partners, in this case, SDN 1 Mangir, it is necessary to provide assistance to improve students' literacy and numeracy skills. The purpose of the service is to improve literacy and numeracy skills in SDN 1 Mangir students through mentoring activities. The methods used include observation, design, implementation, and evaluation. The place of service is held at SDN 1 Mangir. The service instrument used is in the form of observation sheets, reading interest rubrics in the Pojok Literasi, and tests of literacy and numeracy skills. The results of community service activities show that 1) partners respond positively to the implementation of community service activities, 2) the implementation of community service activities are in accordance with the achievement targets, and 3) literacy skills of 92.2% and numeration of 68.7%. Community service activities really help SDN 1 Mangir as a partner in improving students' literacy and numeracy skills.